Male Breast Cancer: A Retrospective Analysis of Clinical and Pathological Features at a Tertiary Care Center - Ambareen, Saima; Rani, Khushboo; H.Kerketta, Zenith; Murari, Krishna (Asian Pacific Journal of Cancer Care, 2024)
Background: Male breast cancer is a rare disease, accounting for approximately 0.5-1% of all breast cancer cases. While recent data suggest a slow rise in incidence, epidemiological data on male breast cancer remains limited compared to female breast cancer due to its rarity. The disease typically presents in older men, often in their sixth or seventh decade of life, and is often diagnosed at an advanced stage with a poorer prognosis than female breast cancer. This study aimed to analyze the epidemiological, clinical, and pathological characteristics of male breast cancer patients. Methods: This retrospective study included 11 male breast cancer patients who presented to the Department of General Surgery at RIMS, Ranchi, over a one-year period. Data regarding clinical history, physical examination findings, family history, disease stage, histopathological examination, and hormonal status were collected and analyzed. Results: The median age at diagnosis was 58.5 years. The average delay in diagnosis was 6.6 months. Of the 11 patients, eight had left breast involvement, and three had right breast involvement. Invasive ductal carcinoma was the most common histological type, seen in nine cases. Ten patients presented with advanced stage T4 disease, while one presented at stage T3. Hormone receptors were positive in 81.8% of cases. Conclusion: Male breast cancer is a rare disease with multiple and diverse risk factors. While it shares similarities in clinical, histological, and prognostic features with breast cancer in women, it also exhibits unique characteristics. To promote early diagnosis and improve prognosis, educational efforts should include teaching self-breast examination to men, advocating for screening mammography in high-risk groups, and testing for familial predisposition. Increased public awareness programs are crucial to educate men about breast cancer and encourage early detection.